2007
DOI: 10.1177/0145721707309808
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Coping, Negative Emotions, and Diabetes Management

Abstract: Psychological, emotional, related behavioral factors, and quality of life are important in diabetes management, are worthy of attention in their own right, and influence metabolic control. A range of interventions that achieve benefits in these areas provide a base for developing versatile programs to promote healthy coping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 159 publications
4
148
0
6
Order By: Relevance
“…Similar study conducted in North West Ethiopia showed that Self-reported adherence to medication measure by MMAS-8 scale was low for 25.4% [49]. Study conducted in Kenyata National Hospital on 171 type 2 diabetes patients; showed that Most patients, 127 (74.3% [53,54].…”
Section: Idf Atlasmentioning
confidence: 87%
“…Similar study conducted in North West Ethiopia showed that Self-reported adherence to medication measure by MMAS-8 scale was low for 25.4% [49]. Study conducted in Kenyata National Hospital on 171 type 2 diabetes patients; showed that Most patients, 127 (74.3% [53,54].…”
Section: Idf Atlasmentioning
confidence: 87%
“…Regardless of type, hyperglycemia resulting from impaired insulinmediated glucose metabolism is a hallmark of diabetes mellitus. Sustained hyperglycemia, a critical component of this life-long disease, damages vasculature throughout the body resulting in many chronic devastating macrovascular and microvascular complications thus negatively impacting patient quality of life [4]. Although heart disease, stroke, and peripheral arterial disease occur in the general population, these macrovascular complications are more likely to occur in diabetic patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…are not self-sustaining, need to be adjusted with modifications in one's condition; that is, initial benefits of DSME intervention may fade by the time of follow-up [46]. In addition, the lifelong and progressive nature of diabetes means that effective diabetes self-management interventions must provide ongoing follow-up booster sessions and supporting activities [47].…”
Section: Preference For Intervention Dosementioning
confidence: 99%